Synthesis of Certain Poly[bis(benzylidene)] Esters and Investigation on their Photocrosslinkability - D. Roop Singh; S. Vasanthi; J. Arul Moli (E-Journal of Chemistry)
Random copolyesters were synthesized directly from respective diacids and diols with diphenylchlorophosphate (DPCP) as a polycondensation agent. These polymers were characterized by FT-IR and NMR spectrometry. Interestingly, they were observed to possess photocrosslinkability which was established using scanning electron microscopy by UV irradiation experiments. Photocrosslinkable polymers have significant applications in the field of non-linear optics, in the generation of photoresists and photorefractive materials.